Moral Flexibility in the Conduct of PKS and PKB Muslim Politicians in West Java (2023–2025) - Nurjanah, Siti; Thohir, Ajid; Darmawan, Dadang (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the mechanisms of moral disengagement and moral flexibility in the political behavior of religious actors in post-reform Indonesia. Moral disengagement is defined as a socio-cognitive process that enables individuals to commit unethical actions without experiencing internal moral conflict, while moral flexibility refers to the contextual and situational application of moral values. Employing a qualitative method with a critical discourse analysis approach, this research analyzes political texts, speeches, ideological documents, and religious narratives that reflect power practices. The research scope includes religion-based political actors and Indonesia’s democratic public sphere. The findings indicate that moral disengagement is institutionalized through euphemistic language, moral justification, and diffusion of responsibility, whereas moral flexibility operates as an adaptive mechanism that alleviates tension between normative values and political interests. The main challenges involve the lack of empirical psychological data and the complexity of discourse interpretation. This study recommends strengthening critical ethical literacy and promoting political leadership models grounded in moral accountability. This research provides a conceptual integration of moral disengagement and moral flexibility within the context of religious politics in Indonesia, contributing to the expansion of moral psychology into the sociology of power.